2013
DOI: 10.1095/biolreprod.112.103515
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Receptor, GPR54, as a Candidate for the Regulation of Testicular Activity in the Frog Rana esculenta1

Abstract: Kisspeptins, acting via GPR54, are new players in the control of reproductive axis. They have the ability to communicate with GnRH neurons sending environmental, metabolic, and gonadal signals, with the induction of GnRH and LH secretion as final effect. At present, the physiological significance of kisspeptin signaling in the gonad is poorly investigated. We cloned GPR54 receptor from the anuran amphibian Rana esculenta testis and investigated its expression in several tissues (brain, spinal cord, ovary, musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 64 publications
12
43
1
Order By: Relevance
“…Phylogenetic and syntenic analyses support the absence of KissR1, KissR2, and KissR3 genes in birds; however, the possible existence of Kissr4 in birds cannot be ruled out due to the incomplete sequencing of bird genomes in the putative region of KissR4 (Pasquier et al 2014). Among tetrapods, amphibians present the largest number of KissR, with three KissR in X. tropicalis (KissR1, KissR2, and KissR3) (Lee et al 2009b), while only the KissR2 transcript has been identified in the bullfrog (Moon et al 2009) and the edible frog (Chianese et al 2013).…”
Section: Jh591432mentioning
confidence: 99%
“…Phylogenetic and syntenic analyses support the absence of KissR1, KissR2, and KissR3 genes in birds; however, the possible existence of Kissr4 in birds cannot be ruled out due to the incomplete sequencing of bird genomes in the putative region of KissR4 (Pasquier et al 2014). Among tetrapods, amphibians present the largest number of KissR, with three KissR in X. tropicalis (KissR1, KissR2, and KissR3) (Lee et al 2009b), while only the KissR2 transcript has been identified in the bullfrog (Moon et al 2009) and the edible frog (Chianese et al 2013).…”
Section: Jh591432mentioning
confidence: 99%
“…Expression levels of kiss and kissr in the brain and, to a lesser extent, in the gonad have been analyzed in several non-mammalian species, including amphibians (Chianese et al 2013) and fish (Mohamed et al 2007, Nocillado et al 2007, Biran et al 2008, Filby et al 2008, van Aerle et al 2008, Kitahashi et al 2009, Mechaly et al 2009, Migaud et al 2012, Alvarado et al 2013, Ohga et al 2013, suggesting a putative role for kisspeptins in controlling reproduction. Moreover, in vivo studies in some teleosts have found that the systemic administration of kisspeptin forms induces detectable biological responses at brain and pituitary levels, with potencies depending on the species (Filby et al 2008, Felip et al 2009, Kitahashi et al 2009, Li et al 2009, Shi et al 2010, Espigares et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the expression of kisspeptin system has also been reported in post meiotic germ cells [Meccariello 2013]. In particular, in human kisspeptin signalling affects sperm motility [23] and lower plasma levels of kisspeptin have been observed in infertile males as compared to fertile males [24][25].…”
Section: Kisspeptins: New Local Modulators Of Testis Activitymentioning
confidence: 99%
“…In this seasonal breeder spermatogenesis starts during late winter-spring with mitotic division of spermatogonia and proceeds during summer with meiotic events; in autumn massive spermiogenesis occurs followed by the winter stasis in which the testis simply contains quiescent primary spermatogonia and newly formed spermatozoa attached to Sertoli cells. During the annual cycle of P. esculentus, Gpr54 fluctuates and is expressed in both Leydig cells and mitotic spermatogonia [19]. Furthermore, in spite no kiss gene has been cloned or characterized in this experimental model, kisspeptin signalling locally induces a wide set of events critical for the upsurge of spermatogenesis onset and the progression of spermatogenesis [20] (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation